Ability to Utilize Digital Health Services: Validation of the Digital HealthCare Scale in Adolescents and Young Adults - Christopher Le; Hanne Søberg Finbråten; Robert Griebler; Diane Levin-Zamir; Øystein Guttersrud (Health Literacy Research and Practice)
Background While adolescents and young adults are increasingly expected to take more responsibility for their health and wellbeing, continuing digital transformation and increased implementation of digital health services (DHS) demand skills to utilize digital solutions offered to successfully undertake self-care and self-management. However, research is lacking regarding measurement of adolescents' and young adults' “ability to utilize DHS” (or “DHC”). Objective This study aims to measure young people's DHC by (1) validating the Digital HealthCare Scale (DHC scale) in adolescents and in young adults and (2) exploring the extent to which DHC and digital health literacy (DHL) are associated with the number of general practitioner, emergency, or specialist visits. Methods A cross-sectional survey was conducted among 890 Norwegian adolescents and young adults age 16 to 25 years. Data were collected from April 2020 to October 2020 using computer-assisted telephone interviewing. Rasch modeling, independent samples t-test, chi-square test, and negative binomial regression models were used to analyze the data. Key Results The DHC scale is considered valid for measuring DHC in adolescents and young adults, showing sufficient unidimensionality, good overall data-model fit, and no disordered response categories nor differential item functioning. Results showed that female participants and adolescents age 16 to 20 years self-reported significantly lower DHL and DHC than male participants and young adults age 21 to 25 years. Regression analyses displayed a statistically significant association between adolescents' and young adults' DHL (n = 371) and DHC (n = 389) and their utilization of specialist health services. For every unit (logit) increase in DHL and DHC, the number of specialist visits decreased by 25% and 28%, respectively. Conclusions Aligned with previous research calling for new up-to-date instruments to measure the new aspects of DHL, our study has introduced a new measurement scale (DHC scale) for use among adolescents and young adults. This scale may be useful for health authorities, public health workers, and health providers in evaluating and adapting DHC. [HLRP: Health Literacy Research and Practice. 2025;9(1):e19–e28.]